Spatial and WTP Development Plan Perencanaan Pembangunan Spal Dan Ipal Untuk Sarana Peningkatan Kualitas Lingkungan Kampung Nelayan Tanjungsari Kabupaten Rembang - widias tuti, iin; Umam, Khotibul; Rochmanto, Decky (Jurnal Civil Engineering Study, 2022)
Domestic wastewater in Kelurahan Tanjungsari has not been properly managed, where the greywater is discharged directly into the drainage. Where the drainage is discharged directly at the sea, causing seawater pollution due to domestic waste. The purpose of this Final Project planning is to design SPAL and IPAL as a means of improving the environmental quality of Tanjungsari Village. The results of the study on the technical aspects showed that the average wastewater discharge of Tanjungsari Village was 69.36 L / person per day. The pipe diameter used in planning the development of SPAL and IPAL for this area is 100 mm or 4 inches. In planning SPAL and IPAL, Tanjungsari Village is equipped with several complementary buildings, namely as follows: 1) Manhole with a size of 70 cm x 70 cm x 100 cm, 2) Grease Trap with a size of 80 cm x 50 cm x 30 cm, 3) Control tub with size 60 cm x 40 cm x 30 cm, 4) Collecting Well with a size of 100 cm x 100 cm x 230 cm, 5) Distribution Box with a size of 100 cm x 50 cm x 130 cm, 6) IPAL 1 room with a size of 500 cm x 300 cm x 300 cm, 7) IPAL 2-5 rooms measuring 300 cm x 300 cm x 300 cm.Budget Plan The cost spent for planning the SPAL and IPAL for Tanjungsari Village is Rp. 3,059,073,121.37.